A knowledge-based perspective on system weaknesses in technological innovation systems. (27th April 2018) - Frishammar, Johan; Söderholm, Patrik; Hellsmark, Hans; Mossberg, Johanna
Abstract: The literature on technological innovation systems (TIS) provides policymakers and other actors with a scheme of analysis to identify system weaknesses. In doing so, TIS analysis centres on which system weaknesses policy interventions should target to promote further development of a particular system. However, prior TIS literature has not sufficiently elaborated on what may constitute the conceptual roots of a 'weakness'. We apply a knowledge-based perspective and propose that many—albeit not all—system weaknesses may root in four types of knowledge problems: uncertainty, complexity, equivocality, and ambiguity. Employing these as sensitizing concepts, we study system weaknesses by analysing data from a biorefinery TIS in Sweden. This analysis results in novel implications for the TIS literature and for achieving a better match between system weaknesses and the design of innovation policies.